Factors affecting Leverage Decision: Empirical Evidence from - Mistry, Dharmendra S.; Vyas, Pallavi C. (Gyan Management Journal, 2021)
Leverage is the extent to which debt is used in company’s capital which has value to take tax advantage and also when benefit out of the assets purchased with the help of the Debt is greater than the cost of the Debt used to finance the Assets. Therefore, the management should determine the requirement of the Debt, examine of the Financial Markets and at the design of the use of leverage in Capital Structure. In the present research work, analysis has been done towards finding out the impact of the independent variables i.e. Firm Size, Asset Tangibility, Profitability on dependent variable i.e. Leverage of Public Oil and Gas Sector in India during the period of 5 years i.e. 2015-16 to 2019-20 through the statistical model. The study revealed that the models fitted have been the best described the behaviour of dependent variable against suitable alternatives and there has been a significant impact of independent variables on Leverage decision.The study found that the independent variables i.e. Firm Size, Asset Tangibility and Profitability have a negative/indirect impact on the Leverage decision.
Keywords: Asset Tangibility; Firm Size; Leverage; Profitability